Survey the Frequency of Organ Donation and Related Factors in Patients with Consciousness Level below 5 in Hospitals of Guilan Province: An Analytical Study - Ali Monfared; Siamak Rimaz; Saeid Anvari; Latif Panahi; Samaneh Ghazanfar Tehran; Somaye Pouy; Keyvan Abdi; Arezo Khiali; Morteza Rahbar-Taramsari; Saman Maroufizadeh (مجله دانشگاه علوم پزشکی گیلان, 2025)
Background: Statistics of accidents, decreased level of consciousness and occurrence of brain death in Iran are high. In this regard, the use of brain death cases in organ transplantation has been carried out in Iran for a long time and several factors are influential in this field. Guilan is the center of organ donation and transplantation in the north of the Iran, a large number of patients hope for transplantation in this center, and limited studies have been conducted in this province. Objective: The present research aims to determine the frequency of organ donation and related factors in patients with consciousness level below 5 in hospitals of Guilan. Methods: In this cross-sectional analytical study, data of all patients with a level of consciousness less than 5 hospitalized in the hospitals of Guilan province between 2021 and 2022 and were included. Information was extracted through the items recorded in the medical files of the patients and the system of the Ministry of Health, Treatment and Medical Education of Iran. After entering the data in SPSS software version 21, data were analyzed using descriptive and inferential statistical tests. Results: The most common outcome of patients was the non-occurrence of brain death (30.9%) and then not being suitable for organ donation (30%). Also, out of 195 cases of brain death, 27 of their relatives (30.7%) did not consent to organ donation. Conclusion: The present study showed that the most common cause of brain death is cerebrovascular causes. Also, despite the fact that a large number of brain cases are eligible for organ donation, organ donation is not done in many cases, and one of the important reasons is the lack of consent of the families. In this regard, proper planning is necessary to improve people's knowledge and attitude regarding the nature of brain death and organ donation.